2013
DOI: 10.1002/cbin.10044
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles, signalling pathways and effects of fluticasone propionate in respiratory syncytial virus‐infected human foetal lung fibroblasts

Abstract: To examine cytokine production in response to RSV infection, we assessed the levels of 29 cytokines released from RSV-infected human foetal lung fibroblasts. We also examined the relationships between the effects of fluticasone propionate and various signalling pathways in the cells. Twenty-four hours after infection (1MOI), RSV-infected cells released cytokines, for example proinflammatory cytokines (IL-1β, IL-6 and TNF-α), anti-inflammatory (IL-1ra), Th1 (IFN-γ, IFN-λ1a, IL-2 and IL-12), Th2 (IL-4, IL-5, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…This is in agreement with previous work showing that prolonged TNF-α production promotes weight loss during an acute RSV infection (152). However, weight loss was not completely abolished by neutralization of TNF-α in FI-RSV-immunized mice, suggesting that additional proinflammatory cytokines such as IL-1α or IL-6 are induced following RSV infection (288), that may contribute to the weight loss associated with FI-RSV VED.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previous work showing that prolonged TNF-α production promotes weight loss during an acute RSV infection (152). However, weight loss was not completely abolished by neutralization of TNF-α in FI-RSV-immunized mice, suggesting that additional proinflammatory cytokines such as IL-1α or IL-6 are induced following RSV infection (288), that may contribute to the weight loss associated with FI-RSV VED.…”
Section: Discussionsupporting
confidence: 92%
“…The representative data of virus infection-associated signaling pathways is shown in Figure 4 . Briefly, a previous report showed that RSV infection in human fetal lung fibroblasts (MRC-5 cells) induces various cytokines through the activation (phosphorylation) of Akt (murine thymoma viral oncogene homolog/protein kinase B), p38MAPK (mitogen activated protein kinase), ERK1/2 (extracellular signal-regulated kinase), and IκB-α (Seki et al, 2013). Human rhinovirus (HRV) infection in human bronchial epithelium cells (BEAS-2B cells) activated p38MAPK, ERK1/2, and NF-κB (nuclear factor kappa B protein).…”
Section: Relationships Between Prrs Signaling Pathways and Cytokinementioning
confidence: 99%
“…Numerous reports show that most respiratory virus infections can induce the production of various types of cytokines in vitro and in vivo (Khaitov et al, 2009; Koetzler et al, 2009; Martínez et al, 2009; Sharma et al, 2009; Ishioka et al, 2011; Lewis et al, 2012; Seki et al, 2013). The findings of previous in vitro studies suggest that influenza virus type A [subtype A(H1N1) virus]-infected human airway epithelial cells produces significant amounts of IL-1, IL-6, and IL-8 (Hofmann et al, 1997).…”
Section: Respiratory Virus Infection-associated Cytokine Productionmentioning
confidence: 99%
“…It has been previously argued that an exogenous or endogenous immunogenic stimulus will activate the innate immune system only if able to induce the release of alarmins, like HMGB1 ( 30 ). By binding to its cognate receptors, HMGB1 modifies cell functions not only with direct autocrine/paracrine activity ( 31 ), but also through indirect potentiation of other inflammatory pathways, e.g., activation of multiple pattern-recognition receptors like TLR2 and TLR4 ( 31 ); release of proinflammatory cytokines like IL-1, IL-6, and IL-8 ( 32 ); and interference with T cell responses inducing TH1 polarization ( 33 ).…”
Section: Discussionmentioning
confidence: 99%